Defect engineering in cast mono‐like silicon: A review. (24th November 2020) - Song, Lihui; Yu, Xuegong
Abstract: Cast mono‐like silicon is a promising material for next‐generation silicon solar cells with higher efficiency and lower cost compared with currently commercialized silicon solar cells. So far, cast mono‐like silicon technique still faces several problems, including multicrystallization, dislocation clusters, sub‐grain boundaries, and impurity contamination, which hinder its mass‐scale applications in photovoltaic industry. In this review, we will introduce these common problems in turn and discuss a multitude of the reported studies on eliminating these problems. Furthermore, light and elevated temperature‐induced degradation (LeTID) was recently reported to be a severe problem of cast mono‐like silicon solar cells, which can cause power loss over 10% relative. This review will introduce the behaviors and the proposed mechanisms of LeTID as well as the methods to suppress LeTID in Section 4. In the subsequent section, the efficiency potential and distribution of cast mono‐like silicon solar cells are discussed. At last, a comprehensive summary will be given for this review. Abstract : This paper reviews the common defects in cast mono‐like silicon, including multicrystallization, dislocations, sub‐grain boundaries, impurity contamination, and the defect responsible for light‐induced degradation. The mechanisms of these defects generation and the methods to suppress them are emphasized. At last, the cell efficiency potential of cast mono‐like silicon solar cells is discussed.